Analysis Financial Feasibility Of Selected Fishing Technology In Bitung Oceanic Fishing Port - Kusumaningrum, Arianda (Sam Ratulangi University, 2022)
Bitung City is one of the production centers as well as the fishing industry in Indonesia. Analysis of the financial feasibility of capture fisheries, especially in PPS Bitung as a fish landing center in Bitung city, needs to be studied scientifically in order to find out the types of fishing gear that are effectively used and can be developed. The purpose of this study is to find out the selected fishing technology that is effectively used, developed, and can prosper the fishing community of Bitung city. Data were collected using survey methods and in-depth interviews with fishermen and local stakeholders. The analysis was carried out on all aspects, namely biological, technical, economic, and social aspects. The scoring method is carried out to determine the fishing unit to get the type of fishing gear that has good performance in terms of various aspects so that it is suitable for development. From the results of this study, it was found that the huhate ranks first because it has a high value from various aspects compared to other fishing gear. This shows that the huhate has a higher business development opportunity than other fishing gear. This is of course closely related to increasing fishery production while maintaining the sustainability of fish resources in Bitung. Although based on the calculation results, the huhate ranks first, it does not rule out the possibility of other fishing gear to become development priorities. Government policies, fisherman culture and social conditions of the local community should be a serious concern in establishing a policy concerning changes in the behavior and understanding of fishermen related to efforts to develop capture fisheries in Bitung.Keywords:Â financial feasibility; fishing; technologyÂ AbstrakKota Bitung merupakan salah satu sentra produksi sekaligus industri perikanan di Indonesia. Analisis kelayakan finansial usaha perikanan tangkap khususnya di PPS Bitung sebagai pusat pendaratan ikan di kota Bitung perlu dikaji secara ilmiah agar dapat mengetahui jenis alat tangkap yang efektif digunakan dan bisa dikembangkan. Tujuan penelitian ini adalah mengetahui teknologi penangkapan ikan terpilih yang efektif digunakan, dikembangkan serta bisa mensejahterakan masyarakat nelayan kota Bitung. Pengumpulan data dilakukan dengan metode survei dan wawancara mendalam baik dengan nelayan maupun stakeholders (pemangku kepentingan) daerah setempat. Analisis dilakukan pada semua aspek yaitu aspek biologi, teknis, ekonomi dan sosial. Metode skoring dilakukan untuk melakukan determinasi unit penangkapan ikan untuk mendapatkan jenis alat tangkap ikan yang mempunyai keragaan (performance) yang baik ditinjau dari berbagai aspek sehingga cocok untuk dikembangkan. Dari hasil penelitian ini didapat huhate menempati urutan prioritas pertama karena memiliki nilai tinggi dari berbagai berbagai aspek dibandingkan dengan alat tangkap lainnya. Hal ini menunjukkan bahwa huhate memiliki peluang pengembangan usaha yang lebih tinggi dibandingkan dengan alat tangkap lainnya. Hal ini tentunya sangat berkaitan dengan peningkatan produksi perikanan sekaligus mempertahankan kelestarian sumberdaya ikan di Bitung. Meskipun berdasarkan hasil perhitungan, huhate menempati urutan pertama, namun tidak menutup kemungkinan alat tangkap lainnya untuk menjadi prioritas pengembangan. Kebijakan pemerintah, kultur budaya nelayan dan kondisi sosial masyarakat setempat hendaknya menjadi perhatian serius dalam menetapkan suatu kebijakan yang menyangkut pada perubahan perilaku dan pemahaman nelayan terkait dengan upaya pengembangan perikanan tangkap di Bitung.Kata kunci: kelayakan finansial; teknologi; penangkapan ikan